Enhancing Mathematics Learners' Experience using Mobile Augmented Reality : Conceptual Framework for the Design and Evaluation - Nur Izza Nabila, Ahmad; Syahrul Nizam, Junaini; Suriati Khartini, Jali (INSIGHT - Indonesian Society for Knowledge and Human Development, 2023)
The application of augmented reality (AR) has been demonstrated, especially in education. However, to our knowledge, no conceptual framework exists to assist in designing effective augmented reality applications for a specific topic in the mathematics curriculum, such as square and square roots. This study proposes a conceptual framework for the design of augmented reality applications for mathematics. Multiple elements were included in the framework, including specification, design, and evaluation. A preliminary study elicited opinions and information from students and teachers. The proposed framework was used as the guideline to develop an augmented reality mobile application for square and square root topics. We later conducted application testing sessions to evaluate the app's usability. The sessions include app demonstration, pre-and post-test, usability testing, and an interview session to assess user satisfaction. Twenty lower secondary students (13 years old; seven males and thirteen females) took part. The findings of the pre-and post-tests and the application's usability and user interface satisfaction test show that the application has been proven effective in learning mathematics. There is a statistically significant difference between the pre-and post-test means. The application effectiveness level is 72.6 percent. Positive responses were also received during the interview. The findings indicate that the suggested framework may serve as a guide for designing future effective augmented reality applications for mathematics learning.